Optimizing Compliance and Reducing Anemia: The Impact of Self-Monitoring Pocket Books on Iron Tablet Intake Among Adolescent Girls at Taruna Utama Vocational School, East Lampung - Besmaya, Beniqna Maharani; Widiawati, Asih; Utami, Iis Tri; Sulistiawati, Yuni (PT FORMOSA CENDEKIA GLOBAL, 2024)
Anemia is a significant health issue among adolescent girls, driven by increased iron needs during growth and menstruation. This study aims to assess the effectiveness of a self-monitoring pocket book in improving compliance with Fe tablet consumption and reducing anemia among adolescent girls at Taruna Utama Vocational School, East Lampung Regency. Using a quantitative quasi-experimental one-group pretest-posttest design, 51 female adolescents were selected through stratified random sampling. Compliance and anemia status data were collected before and after a one-month intervention, during which participants received a pocket book with anemia education and a consumption tracking table. The results show that compliance with Fe tablet consumption increased from 56.9% to 82.4%, and the proportion of non-anemic participants rose from 62.7% to 88.2%. The McNemar test revealed significant improvements in compliance (p = 0.001) and anemia status (p = 0.002).